"And That's a Fact!": The Roles of Political Ideology, PSRs, and Perceived Source Credibility in Estimating Factual Content in Partisan News. Issue 2 (3rd April 2019) - Landreville, Kristen D.; Niles, Cassie
Abstract : Cable news schedule today is programed with a transition between objective reporting and subjective commentary. With this in mind, we address the question: to what extent does political ideology impact one's estimation of factual content in the monologue of a partisan news host? Going beyond direct effects, we analyze two moderated mediation models, using news host as moderator and using parasocial relationship and source credibility as parallel mediators. Results show like-minded partisanship with a news host led to higher estimates of factual content, and this effect worked indirectly through credibility perceptions. Additionally, this process occurred more intensely for conservatives.